A Critical Study About the Preparedness of Elementary Schools for Children with Special Needs (CWSN) - Sharma, Anjali; Bora, Dibyangona (THE PRIMARY TEACHER, 2018)
The purpose of the present study is to explore the preparedness of elementary schools regarding facilities provided to Children with Special Needs (CWSN). To highlight the factual situation on the focus of the study, the authors explored the data supplied by DISE (District Information System of Education) and analysed the data related to enrolment of CWSN, facilities provided to them, and teachers' qualifications who deal with them. It is found that there are sufficient number of CWSN enrolled in schools with a variety of differently-abled students. Still, in this regard, it is reflected that the schools only emphasized providing ramp facilities and ignored other facilities required for other than those physically challenged. Teacher qualifications are a significant issue in truly building inclusive education. It is necessary to include information on the availability of special educators or teachers who have received training to deal with children of different abilities and the particular courses they did or did not. Unfortunately, the DISE data did not include such information in the analytical tables, and state and district transcripts released by the National University of Educational Planning and Administration (NUEPA). This raised the question of whether we are stepping towards establishing inclusive education for differently-abled children; however, schools are not prepared in that way